2020
DOI: 10.3390/genes11111241
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Bov-B LINE Retrotransposons in Snake Lineages Reveals Recent Multiple Horizontal Gene Transfers with Copy Number Variation

Abstract: Transposable elements (TEs) are dynamic elements present in all eukaryotic genomes. They can “jump” and amplify within the genome and promote segmental genome rearrangements on both autosomes and sex chromosomes by disruption of gene structures. The Bovine-B long interspersed nuclear element (Bov-B LINE) is among the most abundant TE-retrotransposon families in vertebrates due to horizontal transfer (HT) among vertebrate lineages. Recent studies have shown multiple HTs or the presence of diverse Bov-B LINE gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 91 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…Kimura divergence analysis of repeat landscaping showed that TEs in snakes were older compared with those of anole lizard TEs [ 25 , 123 ]. Nevertheless, some young elements have also experienced recent expansion in snake genomes, e.g., snake1, CR1, LINEs, and BovB [ 40 , 78 , 125 ]. The CR1 element has also expanded in the crocodilian lineage, constituting around 10% of the total genome.…”
Section: Repeat Abundance In Snake Genomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kimura divergence analysis of repeat landscaping showed that TEs in snakes were older compared with those of anole lizard TEs [ 25 , 123 ]. Nevertheless, some young elements have also experienced recent expansion in snake genomes, e.g., snake1, CR1, LINEs, and BovB [ 40 , 78 , 125 ]. The CR1 element has also expanded in the crocodilian lineage, constituting around 10% of the total genome.…”
Section: Repeat Abundance In Snake Genomesmentioning
confidence: 99%
“…These TEs are important phylogenetic markers in studies investigating the diversity of snake lineages. Recent exploration of a retroelement termed Bov-B LINE shed light on the diversity of snake lineages [ 125 ]. Sequence variability of Bov-B LINE resolved the complex phylogenetic framework among eight diverse snake lineages, including Henophidian (Cylindrophidae, Boidae, and Pythonidae) and Caenophidian (Acrochordidae, Viperidae, Homalopsidae, Elapidae, and Colubridae) snakes.…”
Section: Repeat Abundance In Snake Genomesmentioning
confidence: 99%
“…Our analysis of transposable elements (TEs) shows that they constitute a large proportion of the genomes in four Ixodes tick species, which is typical of large eukaryotic genomes. Interestingly, we identified Bov-B LINEs in the genome of I. ricinus , a subclass of retrotransposons abundant in vertebrates, which have also been found in the genomes of reptile ticks, with evidence of horizontal gene transfer between vertebrates and ticks (Walsh et al 2013; Puinongpo et al 2020). The presence of Bov-B LINE sequences in several species of Ixodes could therefore reflect independent acquisitions of transposons from vertebrate hosts.…”
Section: Discussionmentioning
confidence: 93%
“…3C ); however, there was no difference in fluorescence intensity between the plasmid at 10 −8 ng and the negative control group. The results showed that the lower limit of detection was 31 copies/μL, and the plasmid copy number was calculated using the equation: DNA (copy number) = [(6.023 × 1,023) × (copy number/mol) × DNA amount (g)]/[DNA length (bp) × 660 × (g/mol/bp)], where the base number of recombinant plasmid pMD-19T- B1 was 4,907 bp ( 34 ). The sensitivity of RPA-CRISPR/Cas12a to detect pMD-19T- B1 was 10 times greater than the sensitivity of qPCR ( Fig.…”
Section: Resultsmentioning
confidence: 99%